An Analysis of English for Young Learner Teachers’ Classroom Management - Roslina (JTP - Jurnal Teknologi Pendidikan, 2023)
This current study was a case study that aimed to analyze EYL teachers' classroom management performance at Kolaka Regency, Southeast Sulawesi, Indonesia. Likewise, this study also explored the root problem behind its' limitation. As part of the methodology, five teachers were involved in the observation. All the instrument components were validated throughout the SPSS Program analysis. After the instrument was validated, the classroom interaction process was observed and recorded three times. In addition, the interview session was also gained to ensure the observation result. All the data were analyzed descriptively. The data analysis showed that the EYL teachers in Kolaka Regency had attempted effective planning, teaching technique, and student/teacher relationship simultaneously but not comprehensively. The study also found that the EYL teachers at Kolaka Regency knew the meaning of pedagogic competence as the upstream of classroom management and the effort to implement it. However, they may not be optimal due to their teaching qualities ability. Therefore, the study recommended that there must be much appreciation for EYL teachers. The study also suggested accomplishing a similar study in a larger context to support the EYL teacher's welfare policy.